A Universal Multi-Epitope Vaccine Design Against Porcine Reproductive and Respiratory Syndrome Virus via Bioinformatics and Immunoinformatics Approaches - Xinnuo Lei; Zhi Wu; Qi Feng; Wenfeng Jia; Jun Xie; Qingkang Zhou; Jinzhao Ban; Shanyuan Zhu (Veterinary Sciences)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes reproductive disorders in sows and severe pneumonia in piglets, alongside immunosuppressive effects on the host. It poses a significant global threat to the swine industry, with no effective control measures currently available due to its complex pathogenesis and high variability. Conventional inactivated and attenuated vaccines provide inadequate protection and carry biosafety risks. In this study, we designed a universal multi-epitope peptide vaccine against PRRSV using bioinformatics and immunoinformatics approaches to address these limitations. By selecting sequences from seven representative PRRSV strains, we predicted highly conserved and immunogenic T cell (Th and CTL) epitopes across all encoded proteins. These were rationally concatenated with reported B cell neutralizing epitopes into a multi-epitope vaccine construct. We performed comprehensive assessments of the construct’s physicochemical and biochemical properties, along with predictions and refinements of its secondary and tertiary structures. Molecular docking simulations with TLR2 and TLR4 revealed strong potential binding interactions. Immune simulations indicated that the multi-epitope vaccine could induce robust humoral and cellular immune responses. This study provides a scientific foundation for the development of safe and effective PRRSV subunit vaccines and offers new perspectives for designing vaccines against other viral diseases.